Inovasi Pembuatan Pupuk Organik untuk Mendukung Pertanian Ramah Lingkungan di Desa Tangsi Duren Kecamatan Kabawetan Kabupaten Kepahiang - Reflis Reflis; Redy Badrudin; Rica Denis (Lembaga Pengembangan Kinerja Dosen, 2026)
The rising cost of inorganic fertilizers and their uneven accessibility have encouraged farmers to use nutrient inputs that are locally available, affordable, and safer for the environment. This community service activity was designed to improve farmers' understanding and practical capacity in producing and applying organic fertilizer and eco-enzyme from local organic materials in Tangsi Duren Village, Kabawetan District, Kepahiang Regency. The program applied a participatory approach involving farmer groups, lecturers, and students of the Faculty of Agriculture, Universitas Bengkulu. The activity stages included preliminary observation, coordination with community partners, extension, demonstration, learning by doing, discussion, and evaluation. Conducted on 3 October 2025, the program introduced rice-washing water, fruit peels, vegetable residues, and healthy weeds or wild leaves as raw materials for organic fertilizer and eco-enzyme. The results indicated strong participant enthusiasm, broader awareness of organic farming, and increased willingness to engage in sustainable agriculture development. All participants expressed readiness to support organic farming, although some were still uncertain about its contribution to reducing production costs and improving market access for organic products. Follow-up facilitation with a local environmental care group was initiated to strengthen mentoring and marketing support. This activity confirms that hands-on training based on local resources can serve as an entry point for reducing dependence on chemical inputs and strengthening farmer-based sustainable agriculture.